ON RADIO ANALYTIC MEAN Dd- DISTANCE NUMBER OF SOME MODERN GRAPHS (International Journal of Food and Nutritional Sciences, 2022)
A Radio analytic mean Dd-distance labeling of a connect graph G is an injective function f from the vertex set V(G) to the N such that for two distinct vertices u and v of G,D^Dd (u,v)+⌈|〖f(u)〗^(2 )–〖f(v)〗^(2 ) |/2⌉ ≥1+〖diam〗^Dd (G),where D^Dd (u,v)=D(u,v)+deg⁡(u)+deg⁡(V),D^Dd (u,v) denotes the Dd-distance between u and v diamD^Dd (G) denotes the Dd-diameter of G. The radio analytic mean Dd-distance number of f, 〖ramn〗^Dd (f) is the maximum label assigned to any vertex of G . The radio analytic mean Dd-distance number of f, 〖ramn〗^Dd (G)is the minimum value of G, 〖ramn〗^Dd (G) is the minimum value of 〖ramn〗^Dd (f) taken over all radio analytic mean Dd-distance labeling f of G. In this paper we find the radio analytic mean Dd-distance number of some Modern graphs.